INNOVATIVE ECONOMY AS A FACTOR OF SUSTAINABLE SOCIO-ECONOMIC DEVELOPMENT OF KAZAKHSTAN - R.K. Sabirova; E.M. Adietova; B.B. Korgan (Academic Journal of Physical and Chemical Sciences, 2019)
The key to the formation of a new type of economy in Kazakhstan is large-scale investments in new technologies and the creation of conditions for the constant reproduction of knowledge and their implementation in new high-tech products and services. A large role in the development of the economy is played by information and communication technologies, which are the basis of the country’s new infrastructure. They should develop at a faster pace than the level of economic development. The innovative activity of Kazakhstani enterprises is noticeable in industries that manufacture products with a low degree of processing. Noteworthy is innovative activity in industries where the domestic producer dominates.